The teeth whitening in an age aspect: prevalance of the method use, substantiation of its carrying out and possible complications (clinical research) - Tereshyna, T.; Pakhlevanzade, V. (Journal of Education, Health and Sport, 2021)
The following article presents results of the clinical research on prevalence of use, justification of leading and development of possible complications due to the teeth’ whitening. The main aim of the research is to study prevalence of apply of the teeth’ whitening procedure among patients of different age groups in the Dental Department of the Odessa University Clinic, with a study on indications for leading the aforementioned procedure, as well as complications, that had been developed as a result of it. The research materials are: anamnestic data of patients from the University Clinic, who underwent the teeth’ whitening procedure. Moreover, we had taken into account the following indexes: patient’s age, presence of concominant pathology, the data on leading the teeth’ whitening procedure in the past. The main group was presented by 32 patients, who underwent the aforementioned procedure for the first time in their lives. The group of comparison is represented by 33 patients, who underwent the same procedure couple of times before (once, twice, three times or four times). The research methods: anamnestic, statistical. The methods of whitening, that had been chosen: hardware whitening, laser beam, thermocatalytic whitening and use of chemical catalysts. The analysis of anamnestic data, which was held, make us possible to postulate, that 5% of patients from both groups did not have any complications after the teeth’ whitening procedure. The other patients of the study groups though had a stable pain syndrome, the intensity of which is increasing in 24-48 hours after the procedure and last in average 5-7 days. The folowing article presents a data on a fact, what concominant conditions and diseases of the oral cavity do stimulate a pain syndrome development more often and during what period of time. The current article also describes a character of inner-connections between pain syndrome and gender feature as well as presence of such procedures in the past. The authors had postulated, that the less traumatic and quite efficient method is oxidative cleavage of enzymes, by using which a stable long-lasting effect is reached, as well as there is a lack of pain after the procedure.